2008
DOI: 10.1016/j.jpsychires.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of social anxiety disorder as a risk factor for alcohol and cannabis dependence

Abstract: Social anxiety disorder (SAD) is highly comorbid with alcohol use disorders (AUDs) and cannabis dependence. However, the temporal sequencing of these disorders has not been extensively studied to determine whether SAD serves as a specific risk factor for problematic substance use. The present study examined these relationships after controlling for theoretically-relevant variables (e.g., gender, other Axis I pathology) in a longitudinal cohort over approximately 14 years. The sample was drawn from participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
343
5
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(404 citation statements)
references
References 63 publications
43
343
5
9
Order By: Relevance
“…In previous studies early symptoms of anxiety and depression were related to illicit drug use in adolescence or in young adulthood (Buckner et al, 2008;Wittchen et al, 2007). Our measures of both externalizing and internalizing behavior were based on teacher's evaluations at 12 years of age, whereas other studies collected those symptoms by parents' reports , self-reports (Buckner et al, 2008) or used diagnostic assessments (Wittchen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies early symptoms of anxiety and depression were related to illicit drug use in adolescence or in young adulthood (Buckner et al, 2008;Wittchen et al, 2007). Our measures of both externalizing and internalizing behavior were based on teacher's evaluations at 12 years of age, whereas other studies collected those symptoms by parents' reports , self-reports (Buckner et al, 2008) or used diagnostic assessments (Wittchen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…hyperactivity -impulsivity and inattention (Brook et al, 1996;Monshouwer et al, 2006;White et al, 2001). As internalizing behavior we tested emotional problems, such as depressive symptoms and social anxiety (Buckner et al, 2008;Henry et al, 1993;Jane-Llopis and Matytsina, 2006;Wittchen et al, 2007). The Multidimensional Peer Nomination Inventory (MPNI) Teacher ratings at age of 12 were used.…”
Section: Predictors-mentioning
confidence: 99%
See 1 more Smart Citation
“…A szociális fóbia a klinikai tapasztalatok szerint nagyfokú szenvedéssel jár: szövődményei között gyakoriak a hangulatzavarok (major depresszió 48%), továbbá jellemző az alkoholizmus (48%), az evészavarok (42%) és a drogfüggőség (29%) [1,[9][10][11]. Ha a szociális szorongás krónikussá válik, a személy igyekszik elkerülni a társas helyzeteket, és ez akár tartós munkaképtelenséghez is vezethet [2][3][4][5][6].…”
unclassified
“…Recently, researchers have identified that individuals with SAD appear particularly vulnerable to marijuana-related problems too. Data from the National Comorbidity Study suggest that individuals with SAD are 7 times more likely to experience marijuana dependence relative to the general population (Agosti et al, 2002) and undergraduates with higher social anxiety appear to be particularly vulnerable to marijuana use problems (Buckner et al, 2007;Buckner et al, 2008a). In a study, adolescents with SAD were nearly 5 times more likely to develop marijuana dependence as young adults compared to adolescents without SAD (Buckner et al, 2008b).…”
Section: Co-morbiditymentioning
confidence: 99%